Accommodation of Silicon in an Interconnected Copper Network for Robust Li‐Ion Storage. (20th February 2020) - Liu, Yanyan; Sun, Minghao; Yuan, Yifei; Wu, Qiang; Wang, Hongxun; He, Yi; Lin, Zhan; Zhou, Fengli; Ling, Min; Qian, Chao; Liang, Chengdu; Lu, Jun
Abstract: Silicon (Si)‐based materials are one of the most promising anodes to be applied in rechargeable lithium ion batteries. However, the active Si/electrolyte interface causes continuous side reactions and poor conductivity, which significantly decreases the cycling stability. Cu is the only metallic current collector that has been known to promote electron conduction and lithium‐ion transfer without alloying reaction occurrence. However, to the best current knowledge, scalable interface engineering incorporating Cu has not been reported. Herein, this conductive Cu interface (CCI) is constructed through a self‐assembly carbothermic reduction method to achieve efficient protection of Si/electrolyte interfaces while allowing for fast Li + diffusion. The energy barrier of lithium‐ion diffusion through Cu is calculated to be 0.1965 eV, which is much lower than that through Au, Fe, and Ni films. Benefiting from the enhanced interfacial protection and kinetics of Si with CCI, a fading rate of only 0.068% is maintained for 1000 cycles and an aerial capacity of 4.78 mAh cm −2 is achieved after 280 cycles, which is comparable to the industry standards required for practical application. Abstract : A nanoscale conductive copper interlayer (CCI) is fabricated onto Si nanoparticles via a self‐assembly carbothermic reduction method. Introduction of CCI in Si anodes not only enhances the interfacial stability of Si anodes during long‐term cycling in lithium‐ion batteries but also facilitates fast electron/ion transfer thus improving the electrochemical kinetics of the electrode.